Multiple logics in financialisation? Moving to carbon sustainability in build-to-rent development - Wainwright,T; Demirel,P (Environment and Planning A: Economy and Space, 2023)
Real-estate has become an integral part of financialised economies, but while scholars have turned to examine the emergence of carbon markets, the role of carbon in real-estate finance has been broadly overlooked. Real-estate as a sector has been historically slow to innovate, particularly in response to pressure from climate change. More recently, the attitude of UK build-to-rent (BTR) developers to carbon is changing, partly due to global initiatives including the United Nation's Sustainable Development Goals (UNSDGs), but also pressure from institutional investors. In this paper, we provide nuanced insight into the emergence of new logics within financialisation's governance in the UK BTR sector and examine how investors attempt to steer developers into adopting low carbon building materials and designs, while identifying barriers. First, we highlight the multiplicity of financialisation's logics wrapped within assets, highlighting the presence of a carbon logic, which creates pressure for low-carbon activity. Second, we contribute to debates on assetisation and financialisation by examining the tools and knowledge used to create low-carbon real-estate assets, and how carbon attributes are ‘retrofitted’ into existing asset classes.